Alkali activation of recycled concrete and aluminum salt slag aggregates for semi-rigid column inclusions. (22nd February 2023) - Lin, Youli; Maghool, Farshid; Arulrajah, Arul; Horpibulsuk, Suksun
Highlights: A novel semi-rigid inclusion column system for ground improvement of soft soils. Alkali activation of recycled concrete and aluminum salt slag aggregates as stone column materials. Evaluation of unconfined compressive strength with respect to different material compositions and curing conditions. Permanent deformation responses of geopolymer-stabilized semi-rigid inclusion column under cyclic loading. Acceptable strength development for ground improvement work. Abstract: Stone columns develop their load-bearing capacity from the circumferential confinement offered by the surrounding soils. In highly plastic soils, the circumferential confinement provided by the surrounding soft soils may not be sufficient to develop the required bearing capacity. Meanwhile, the ground improvement industry has been keen to explore substitution backfill materials due to the depletion of natural aggregate resources typically used to construct stone columns. This research investigated the viability of using recycled concrete aggregate (RCA) and recycled aluminum salt slag (RASS), stabilized with alkali-activated fly ash (FA), slag (S) and a binary precursor (FA + S), as a novel semi-rigid inclusion column system for ground improvement of soft soils. The effect of the RCA/RASS ratios, additive types and dosages along with different curing conditions on the unconfined compressive strength (UCS) of geopolymer-stabilized mixtures, were evaluated. Various reinforcing mechanisms were suggested through the microstructure characterization of the mixtures. In addition, the permanent deformation responses of mixtures under cyclic loading were studied using repeated load triaxial (RLT) tests that simulate the cyclic moving traffic loads imposed on the stone columns system. The results demonstrated that increasing the RASS contents resulted in a subsequent decline in the UCS of the mixtures. Increasing the additive dosages on the other hand, in general led to higher strengths. The effects of both curing duration and temperature were found to play a vital role in the strength development of the mixtures. Furthermore, 100RCA stabilized by as low as 5% alkali-activated FA, S or (FA + S), met the minimum UCS requirement of 1.034 MPa for ground improvement. The highest reduction in permanent strain of 87.3% was recorded for the stabilized 100RCA + 10%(FA + S) mixture compared to the unbound 100RCA (control group). The practical implications of the findings were also discussed in detail throughout the paper.